Starość nie znaczy bierność - współczesne metody aktywizowania seniorów (dokument dostępny po zalogowaniu tylko dla osób z dysfunkcją wzroku) - Rokicki, Andrzej (Lublin: Uniwersytet Marii Curie-Skłodowskiej)
The article makes an attempt to reflect on the problem that stems from the fact of ageing of societies. Whether the autumn of life means passivity or whether it is appropriate to experience this particular stage of life actively. The paper also gives the outline of how senility was dealt with over the centuries and how it is perceived nowadays. The author has also presented some ways of stimulating seniors to activity, showing beneficial effect of widely understood activation.
Keywords: starość; aktywizacja; Uniwersytet Trzeciego Wieku; senelity activation; the University of the Third Age